SURVEI FAKTOR KULTUR TEKNIS TERHADAP PERKEMBANGAN POPULASI HAMA PENGGEREK BUAH KOPI Hyphotenemus hampei Ferr (Coleoptera:Scolytidae). DI KABUPATEN SIMALUNGUN - Fitri Ace Samosir; Mena Uly Tarigan; Syarial oemry Syarial oemry (Jurnal Agroekoteknologi, 2013)
Fitri Ace Samosir, "Survey of Progress Against Technical Factors Population Culture Pest Fruit Borer CoffeeHyphotenemus hampei Ferr. (Coleoptera: Scolytidae) in the District Simalungun " under the guidance of MenaUly Tarigan and Syarial Oemry. This research intends to determine the population of the coffee fruit borer H.hampei in some coffee plantations in the Kingdom Simalungun are Raya District, Pane District, Purba District.This research used quantitative analysis of the correlation Population Correlation H. hampei ( X) with theintensity of the attacks on coffee plants ( Y) and correlation with the population of the coffee plantmaintenance H. hampei. The results showed that there were differences in population and the intensity of thecoffee fruit borer attack H. hampei in the district of Simalungun due to differences in height. Population of H.hampei in the Raya District is 148.83 pest, in the Pane District pests as much as 145.20 and 24.10 in the districtof Purba as pests. Intensity of attacks in the Raya District H.hampei at 83.50%, in the Pane District at 88.83%,and in the Purba District of 26.83%.Keywords: Coffee plant and Hyphotenemus hampei Ferr.